Objective Assessment of the Long-Term Volumizing Action of a Polycaprolactone-Based Filler - Angelo-Khattar M (Dove Medical Press, 2022)
Maria Angelo-Khattar1,2 1American Academy of Anti-aging Medicine, Dubai, United Arab Emirates; 2Altaderma Clinic, Dubai, United Arab EmiratesCorrespondence: Maria Angelo-Khattar, Tel +971506245494, Email maria.khattar@altaderma.comBackground: The polycaprolactone-based filler, (PCL-1, Ellansé-S), forms part of the recently growing portfolio of biodegradable collagen-stimulating fillers. It is comprised of a suspension of 25- 50 micron diameter microspheres of polycaprolactone (PCL) (30%) in a carboxymethyl cellulose (CMC) gel carrier (70%) and has gained popularity due to its long-term volumizing action.Objective: This study outlines a retrospective case series of nine patients injected with the PCL-1, for volume augmentation in the mid-face. Objective volume calculations were performed with the Canfield Vectra 3D Imaging System at two time points post-implantation, with the objective of determining the longevity of the volumizing effect of the bio-stimulating substance.Results: A clear increase in volume, between 50- 150%, was found in all of the patients at two years, over and above the volume initially injected. All the patients were satisfied with the longevity of the results.Discussion: The PCL-based filler is believed to afford immediate volume restoration due to the CMC gel component and a long-term action due to neo-collagenesis, induced by the PCL microspheres. The CMC gel is known to dissipate within 6- 8 weeks, only to be replaced by new collagen induced by the PCL particles. Thus soft-tissue formation induced by the PCL particles, ultimately leads to a sustained volumizing effect.Conclusion: The PCL-based filler is shown to have a sustained volumizing effects of at least 2 years duration with clear evidence of increase in volume over and above the volume injected, in all of the cases studied. This is indicative of significant neo-collagenesis induced by the PCL microspheres.Keywords: polycaprolactone, biostimulant, Vectra 3D